Hearing and sociality: the implications of hearing loss on social life - Podury, Archana; Jiam, Nicole T.; Kim, Minsu; Donnenfield, Jonah I.; Dhand, Amar (Frontiers in Neuroscience, 2023)
Hearing is essential to the formation of social relationships and is the principal afferent of social life. Yet hearing loss, which is one of the most prevalent forms of sensory disability worldwide and is critical for social development, has received little attention from the social interventionalist perspective. The purpose of this mini-review is to describe the basic neurobiological principles of hearing and to explore the reciprocal relationships between social support, hearing loss, and its psychosocial comorbidities. We also discuss the role of social enrichment in sensorineural recovery and identify open questions within the fields of hearing physiology and social networks.